(untitled) (Research, Society and Development, 2021)
Objective: To review the available scientific literature, in order to synthesize some forms of adjuvant treatment available in the management of patients with FG. Methods: research on some indexing platforms, a total of 17 articles, published in the last 7 years, which related to adjuvant methods to the treatment of Fournier’s Gangrene, in particular hyperbaric oxygen therapy and wound treatment therapy with the use, were selected of negative pressure. Results and Discussion: The methods used as adjuvants for wound closure contribute positively to the recovery of patients with FG, when reported after indication. The wound closure therapy assisted in the reduction, if useful in controlling the environment of recovery from the injury and reducing the time of clinical treatment without interfering in the mortality of the disease. Hyperbaric oxygen therapy has a direct antibacterial effect on anaerobics, improves the phagocytic action of neutrophils, increases angiogenesis and reduces edema. Negative pressure therapy is used in the acute and repair phases, accelerating the appearance of granulation tissue. Conclusion: The use of adjuvant methods to the treatment of Fournier’s Gangrene is promising and, with exceptions, demonstrate better wound recovery when compared to patients who do not use them, and after professional and individualized clinical evaluation of the cases, such methods can be allies in the recovery of the sick.